PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL: STUDI TENTANG FAKTOR PENDUKUNG DAN PENGHAMBAT - Mambaul usulil khikmah AS; Isyatil Fitri; Ainul Rofiqo; Nurul Fajriah Wati (Journal Multicultural of Islamic Education, 2026)
This study aims to identify and analyze supporting and inhibiting factors in the implementation of multicultural-based Islamic Religious Education (PAI) learning in educational settings. This study used a qualitative approach with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation, involving school principals, PAI teachers, and students as informants. Data analysis employed an interactive model encompassing data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation. The results indicate that supporting factors for multicultural-based PAI learning include teacher competence in understanding and integrating diversity values ​​into learning, school policies supporting inclusive education, a heterogeneous learning environment, and the use of contextual and participatory learning methods and media. Furthermore, attitudes of tolerance, openness, and mutual respect among students contribute to the successful implementation of this learning. Inhibiting factors include teachers' limited understanding of the concept of multiculturalism, a lack of professional training and mentoring, the limited availability of multicultural-based teaching materials, and the persistence of stereotypes, prejudice, and the potential for social conflict among students. Furthermore, suboptimal institutional support also hinders the implementation of this learning.